The Influence of Technology on Management and Legal Aspects of the Tourism Business - Purnama, Yulian; Rusmini, Andin (PT. LITERASI SAINS NUSANTARA, 2023)
Tourism is one of the fastest growing economic sectors in various countries around the world. In the last decade, the development of ICT has significantly changed the landscape of tourism business. The influence of technology on management and legal aspects in the tourism business is becoming an increasingly important topic to research. This research aims to examine the influence of technology on management and legal aspects in tourism business. This research adopts a qualitative approach through literature analysis, which means that this research will investigate and explain information and content sourced from various documents and texts as the basis for analysis. The study results show that the influence of technology in the tourism business has significantly changed the landscape of this industry. The management of tourism companies has undergone major changes, with online booking, data analytics, better communication, and more efficient inventory management. Along with that, the legal aspects of tourism business have faced new challenges with increasingly stringent regulations on data protection, e-commerce, international travel regulations, and corporate social responsibility.